Establishment of novel options for quantification of bioactive compounds via planar chromatography effect-directed analysis combined with nuclear magnetic resonance spectroscopy - Azadniya, Ebrahim; Justus Liebig University Giessen (My University, 2019)
Hyphenation between high-performance thin-layer chromatography and effect-directed analysis (HPTLC-EDA) via immersion/spraying is a simple and fast procedure for bioprofiling to find the responses of known and unknown compounds in situ a complex sample matrix. In order to benefit the bioanalytical potential of HPTLC-EDA, several obstacles of the automated immersion needed to be avoided such as the (1) required high volumes of solutions, (2) tailing or shifting zones, (3) gradual inactivation of the re-used enzyme solution, and (4) lack of covering the whole plate surface. Using automated piezoelectric spraying for performing an assay was an alternative but challenging and we reached this milestone that via optimization of important aspects i.e. plate pre-wetting, type of spraying nozzle and applied volumes. To overcome above challenges, piezoelectric spraying provided (1) using by a factor of 4-27 less solutions consumption than by immersion (cheaper and green workflow), (2) better resolved autogram zones and no zone shift (better quantification), (3) covering the whole plate surface (both sides development) and (4) using always a fresh solution (defrost an aliquot of enzyme solution) as the best practice with regard to the standardization of HPTLC-EDA procedure. Finally, the newly developed automated piezoelectric spraying procedures for the application of biological (Aliivibrio fischeri) and enzymatic acetyl- and butyrylcholinesterase (AChE/BChE) assays were used for bioprofiling of Peganum harmala seed extract. By their in situ high-resolution mass spectrometry (HRMS) spectra, the active zones were assigned to be harmine, harmaline and ruine as AChE inhibitors and harmol, vasicine and deoxyvasicine as BChE-inhibitors.
Keywords: HPTLC; bioassay; quantitative NMR spectroscopy; enzyme inhibitory equivalency calculation; thresholds of toxicological concern (TTC); ddc:540